Union économique et monétaire et État-Providence : la subsidiarité en question (Note) - Richez-Battesti, Nadine (Études internationales, 1996)
This article seeks to analyze the social impacts of the Economic and Monetary Union and to reflect on the new modalities for producing social norms within this new context. First, after pointing out limits to the nominal convergence that the treaty stipulates for the interim phase, we mil present the new forms of adjustment pursuant to the EMU and their impacts on the welfare state. We will then turn to the responses of some economists to the introduction of a single currency and coordination of budgetary policies, including fiscal federalism. We will try to show the desirability of a European welfare state that would introduce some coherence between the different levels (local, national, Europe-wide) and forms (legislative and union-management) of social regulation ; in essence, a reworking of the idea of social subsidiarity.